The Paleogene Tectonostratigraphy Of Northern Part Masalima Trench Basin - Siringoringo, Luhut Pardamean; Noeradi, Dardji (UIR PRESS, 2016)
Northern part of Masalima Trench Basin is located in the southern part of the Strait of Makassar, which includes Masalima Trough and Massalima High. The area of research is an extension of the South Makassar Basin which extends from South Makassar Basin to the Northeast part of Java Sea. Subsurface data are used such as 2D seismic sections (21 lines) and data drilling wells (2 wells) to understand the tectonic structure in the basin formation and understand the stratigraphic order of basin. Based on well data can be known that Northern part Masalima Trench Basin is aborted rift because marked by post rift phase. Northern part Masalima Trench Basin was formed by normal faults which have trend northeast-southwest with  pre rift, early syn rift, late syn rift, and post rift sediment geometry. Early syn rift sediment was Middle Eocene, late syn rift sediment was Middle Eocene till Early Oligocene and post rift sediment was Early Oligocene till Early Miocene. The Depositional environment of early syn rift phase such as beach, shallow marine, and land. The Depositional environment of late syn rift phase such as beach till deep marine, and the depositional environment of post rift is deep marine.